Complete chloroplast genome of a novel chlorophyll-deficient mutant (clm) in sweetpotato (Ipomoea batatas L.). Issue 3 (4th March 2021) - Zou, Hongda; Zhang, Xiongjian; Chen, Jingyi; Wang, Zhangying; Huang, Lifei; Fang, Boping
Abstract: The complete chloroplast genome of a novel chlorophyll-deficient mutant ( clm ) and its wild type (WT) in sweetpotato ( Ipomoea batatas L.) was sequenced. The complete chloroplast genome of clm and WT was 161, 393 bp and 161, 429 bp in length, containing a large single copy (LSC) region of 87, 561 bp and 87, 597 bp, respectively, a small single copy (SSC) region with the same length of 30, 890 bp and a pair of inverted repeat regions (IRs) with the same length of 12, 052 bp. Both of them contained 132 genes including 87 protein-coding sequences, 37 tRNA, and eight rRNA. Comparing to the WT, four SNPs and three INDELs were detected and only one INDEL in the exon affecting the translation of rpoA gene. Phylogenetic analysis showed that clm and WT were closely related to Ipomoea tabascana . The complete chloroplast genome of clm and its WT will play a role in understanding the molecular mechanism of chlorophyll deficiency and developing molecular markers in sweetpotato.